10-year experience of Paediatric varicocele embolization in a tertiary centre with long-term follow-up. Issue 2 (April 2022) - Wong, Simon; Vigneswaran, Ganesh; Maclean, Drew; Bryant, Timothy; Hacking, Nigel; Maher, Ben; Somani, Bhaskar; Manoharan, Sengamalai; Brownlee, Ewan; Griffin, Stephen; Modi, Sachin
Summary: Introduction: Paediatric varicocele embolization has many benefits over surgical ligation, but lacks published long-term data. We investigated technical and clinical outcomes in this under reported patient group. Objective: To evaluate technical success, complications and recurrence rates following varicocele embolization in paediatric patients. Materials and methods: A single-centre retrospective review of procedural data and electronic notes of consecutive patients referred for varicocele embolization over a 10-year period was performed (February 2010–March 2020). The primary outcomes were technical success and clinical efficacy (lack of symptom recurrence). Secondary outcomes included complications, testicular vein size reduction and procedural parameters including radiation exposure. Chi-square analysis was used to identify predictors of clinical success. Follow-up involved outpatient clinical assessment and telephone interview. Results: 40 patients (median age 15) were referred for left-sided symptomatic varicocele. Technical embolization success was achieved in 36/40 patients (90%), with 4 procedures abandoned (inaccessible vein). Embolization technique was platinum-based coils ± sclerosant. There were no immediate or long-term procedural complications. 32/36 patients completed short term follow-up at a median interval of 2.8 months. 30/32 (93.78%) experienced early clinical success. We found a significant reduction in peritesticular vein size following embolization (pre-3.70 vs post-2.56 mm, p = 0.00017) and a significant relationship between varicocele grade and early clinical success (χ2 = 4.2, p = 0.04), but not pre-treatment peritesticular vein size (χ2 = 0.02, p = 0.88). 33/36 patients completed long-term follow-up (median 4.2 years, range 0.36–9.9 years) producing a late clinical success rate of 93.9% (31/33). No post procedural complications including hydroceles were identified. Discussion: This study demonstrates technical success, matching rates described in adult patients which is reassuring and in support of embolization in the younger patient cohort. More importantly, the overall clinical success rate is comparable with previous embolization studies. Reassuringly, all symptom recurrences occurred early in follow-up, and there is a cogent argument for a single follow-up appointment at this juncture. Our long-term average follow-up duration, primarily gained via telephone interview, exceeds other studies. Although our study has the longest follow-up for varicocele embolization in children, it is limited by a few patients being lost to early and long-term follow-up. This is a recognised issue faced by studies attempting to follow-up benign conditions with a high clinical success rate. Conclusion: Paediatric varicocele embolization is a successful alternative to surgical ligation, with no complications and good clinical outcomes over a long-term follow-up. Summary Table Study outcomes with average follow-up length. Summary Table N Average age, range Technical success Clinical success Recurrence Complications Average follow-up length, range 40 15 (mean), 12-17 90% (36) 94% (31) 3% (1) 0 4.2 years (median), 0.4–9.9 years